Strategi Pengembangan Pariwisata Halal Kota Medan dengan Mengoptimalkan Industri Kreatif - Sayyidina, Sayyidina; Zahra, Karina; Purba, Enjel Elfrida; Lubis, Putri Kemala Dewi (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to determine the potential for halal tourism in the city of Medan, and look for creative industry development strategies that can be used in developing halal tourism in the city of Medan, especially in the Al-Mashun Grand Mosque Area. This research uses quantitative, qualitative descriptive analysis, and the analysis technique used is SWOT analysis. The research results show that the Al-Mashun Grand Mosque area is ready to become a halal tourist area in Medan. The Al-Mashun Grand Mosque area is supported by several creative industries such as culinary, fashion and malls which have complied with Halal tourism requirements such as the availability of a Halal Logo or certification, the availability of prayer and ablution rooms, clean toilets, appropriate waiter clothing. Strategy for product development in the area The Al-Mashun Grand Mosque is part of the awareness to maintain and maintain halal tourism. Even though the Al-Mashun Grand Mosque area is ready to become a halal tourist destination in Medan, it still needs support from the local government for halal certification because there are still restaurants and eating places in the area that do not have halal certification or logos and create halal tour packages to increase the number of tourists. Muslims to visit the Al-Mashun Grand Mosque area. The role of the community is also important in maintaining and maintaining the development of halal tourism in the Al-Mashun Grand Mosque area.